Adaption of smart applications in agriculture to enhance production - Subhrajit Mandal; Anamika Yadav; Florence A. Panme; Kshetrimayum Monika Devi; Shravan Kumar S.M. (Smart Agricultural Technology, 2024)
Food security has grown into a serious concern in all countries around the globe due to the growing population, the depletion of renewable resources, the loss of agricultural farmlands, as well as the rise in uncertain weather conditions. Due to these issues, the agricultural sector is moving towards “smart agriculture,” which utilises the Internet of Things (IoT) and artificial intelligence (AI) to optimise operations and increase production. Several innovative technologies and approaches are integrated into the IoT and AI, including large amounts of data, sensing technology, networking, cloud computing, and apps for end-users. The objective of this study is to examine current developments in smart applications utilizing the IoT and AI technology for smart agriculture. It also highlights the open problems and difficulties associated with smart applications in smart agriculture, as well as the trends and prospects in this field. Furthermore, this study will help to determine how IoT and AI applications may be incorporated into the smart agricultural industry. The results of this study will serve as valuable information for future research and development of IoT and AI solutions to raise the quality standards and profitability of the agriculture industry. Smart application techniques would provide quick and safe large-scale classification with the benefits of immediate availability of data, adaptability, ease of operations, and precise spatial resolution to increase production and require the least amount of energy and time.